KAJIAN HUKUM DAN MASYARAKAT (SEBUAH PENGANTAR) - Pudjo Utomo (Qistie Jurnal Ilmu Hukum, 2012)
Consciously  or  not  influenced  by  living  together  human  precepts  which will curb transportaion and set it between humans. Policies live together gave ancer-ancer  deed  whereby  may  run  and  deeds  which  must  be  avoided. Regulation of life is instructive to  humans he should behave in public, and acts and force is set to ensure the discipline in society is called the rule of law.Kata kunci : Hukum, Masyarakat, Ketaatan Hukum, Psikologi Hukum.